2019
DOI: 10.3389/fspor.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

Walking Cadence Affects the Recruitment of the Medial-Lateral Balance Mechanisms

Abstract: We have previously identified three balance mechanisms that young healthy adults use to maintain balance while walking. The three mechanisms are: (1) The lateral ankle mechanism, an active modulation of ankle inversion/eversion in stance; (2) The foot placement mechanism, an active shift of the swing foot placement; and (3) The push-off mechanism, an active modulation of the ankle plantarflexion angle during double stance. Here we seek to determine whether there are changes in neural control of balance when wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 67 publications
2
42
1
Order By: Relevance
“…It was discussed later both in robotics (Kuo, 1999;Pratt et al, 2006) and human motor control (Bauby and Kuo, 2000;Hof, 2008) and is now widely accepted to be one of the dominant mechanisms for human balance control during walking (Wang and Srinivasan, 2014;Bruijn and van Dieën, 2018;Reimann et al, 2018a). The lateral shift of the left foot before heel-strike can be generated by a left hip abduction, but also by a combination of internal rotation of the stance leg knee and external rotation of the swing leg hip joint, and we have found evidence for both (Reimann et al, 2018b;Fettrow et al, 2019). We quantify the foot placement shift by calculating the difference between the perturbed foot placement and the predicted foot placement based on the CoM position and velocity at mid-swing using a linear model fitted to the unperturbed steps (for details see Wang and Srinivasan, 2014;Bruijn and van Dieën, 2018;Reimann et al, 2018b).…”
Section: Foot Placementsupporting
confidence: 57%
See 3 more Smart Citations
“…It was discussed later both in robotics (Kuo, 1999;Pratt et al, 2006) and human motor control (Bauby and Kuo, 2000;Hof, 2008) and is now widely accepted to be one of the dominant mechanisms for human balance control during walking (Wang and Srinivasan, 2014;Bruijn and van Dieën, 2018;Reimann et al, 2018a). The lateral shift of the left foot before heel-strike can be generated by a left hip abduction, but also by a combination of internal rotation of the stance leg knee and external rotation of the swing leg hip joint, and we have found evidence for both (Reimann et al, 2018b;Fettrow et al, 2019). We quantify the foot placement shift by calculating the difference between the perturbed foot placement and the predicted foot placement based on the CoM position and velocity at mid-swing using a linear model fitted to the unperturbed steps (for details see Wang and Srinivasan, 2014;Bruijn and van Dieën, 2018;Reimann et al, 2018b).…”
Section: Foot Placementsupporting
confidence: 57%
“…This mechanism was first noted in walking by Hof et al (2007) and later confirmed as an active mechanism (Hof et al, 2010;Reimann et al, 2017Reimann et al, , 2018bHof and Duysens, 2018). The roll torque is generated by an activation increase in the medial ankle muscles (tibialis anterior, gastrocnemius medialis) and a decrease in the lateral muscles (peroneus longus) (Reimann et al, 2018b;Fettrow et al, 2019). We quantify this mechanism by integrating the difference in the subtalar joint angle between the perturbed and unperturbed steps over single stance.…”
Section: Ankle Rollmentioning
confidence: 90%
See 2 more Smart Citations
“…The nervous system combines these mechanisms in different ways to maintain balance, as the use of each mechanism varies on any given step (Fettrow et al, 2019b). Furthermore, the relative use of the mechanisms is altered based on internal constraints, such as the phase of the gait cycle (Reimann et al, 2019), or the stepping cadence (Fettrow et al, 2019a). This allows for a highly flexible system that can meet the goal of maintaining balance during locomotion through a variety of scenarios.…”
Section: Introductionmentioning
confidence: 99%